Ideally Hexagonally Ordered TiO2 Nanotube Arrays. Issue 4 (4th July 2017) - Sopha, Hanna; Samoril, Tomas; Palesch, Erik; Hromadko, Ludek; Zazpe, Raul; Skoda, David; Urbanek, Michal; Ng, Siowwoon; Prikryl, Jan; Macak, Jan M.
Abstract: Ideally hexagonally ordered TiO2 nanotube layers were produced through the optimized anodization of Ti substrates. The Ti substrates were firstly covered with a TiN protecting layer prepared through atomic layer deposition (ALD). Pre‐texturing of the TiN‐protected Ti substrate on an area of 20×20 μm 2 was carried out by focused ion beam (FIB) milling, yielding uniform nanoholes with a hexagonal arrangement throughout the TiN layer with three different interpore distances. The subsequent anodic nanotube growth using ethylene‐glycol‐based electrolyte followed the pre‐textured nanoholes, resulting in perfectly ordered nanotube layers (resembling honeycomb porous anodic alumina) without any point defects and with a thickness of approximately 2 μm over the whole area of the pattern. Abstract : Line 'em up : Protection of the Ti surface with a TiN layer followed by its focused ion beam patterning leads to ideal hexagonal ordering of TiO2 nanotube layers upon anodization.